2015 11th European Dependable Computing Conference (EDCC) 2015
DOI: 10.1109/edcc.2015.25
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Energy Footprint of a Distributed Consensus Algorithm

Abstract: Abstract-The Raft consensus algorithm is a new distributed consensus algorithm that is both easier to understand and more straightforward to implement than the older Paxos algorithm. Its major limitation is its high energy footprint. As it relies on majority consensus voting for deciding when to commit an update, Raft requires five participants to protect against two simultaneous failures. We propose two methods for reducing this huge energy footprint. Our first proposal consists of adjusting Raft quorums in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Many companies have found that Raft is easy-toimplement and provides good performance. Pâris et al reduced energy footprint of Raft [34]. Gramoli et al put forward a fast consensus-based dynamic reconfigurations method which can speedup a primary-based rolling upgrade [18].…”
Section: Related Workmentioning
confidence: 99%
“…Many companies have found that Raft is easy-toimplement and provides good performance. Pâris et al reduced energy footprint of Raft [34]. Gramoli et al put forward a fast consensus-based dynamic reconfigurations method which can speedup a primary-based rolling upgrade [18].…”
Section: Related Workmentioning
confidence: 99%
“…The significant additional contribution of our approach lies in incorporating BFT. Markov analysis is performed in [22] as well for a more specific setup to evaluate the protection against data loss and availability for two main improvements on Raft consensus algorithm. The approach presented in this study can be adopted for similar consensus algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that reducing the energy footprint of the RAFT protocol is essential to ensure its continuous success. We addressed the issue in a previous paper [14] and proposed two approaches for reducing the number of servers involved in a Raft cluster without significantly altering the Raft algorithm [14]. Our first proposal consisted of adjusting Raft quorums in a way that would allow updates to proceed with as few as two servers while requiring a larger quorum for electing a new leader.…”
Section: Introductionmentioning
confidence: 99%